Prioritizing Value Chains for Agri-Food System Development in Egypt: The Agriculture Investment for Development Analyzer (AIDA) as an innovative strategy, policy and investment planning tool - Breisinger, Clemens; Raouf, Mariam; Thurlow, James; Wiebelt, Manfred (2019)
as part of the IFPRI-Egypt Seminar Series- funded by the United States Agency for International Development (USAID) project called “Evaluating Impact and Building Capacity” (EIBC) that is implemented by IFPRI.